1980
DOI: 10.1002/1097-0142(19800415)45:8<2061::aid-cncr2820450813>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetence, immunosuppression, and human breast cancer. II. Further evidence of initial immune impairment by integrated assessment effect of nodal involvement (N) and of primary tumor size (T)

Abstract: Comprehensive immune function by integrated score was assessed in 158 operable, 55 inoperable, and 52 metastatic breast cancer patients relative to 107 healthy controls. The score was derived from in vivo response to PPD and DNCB and in vitro lymphocyte stimulation by PPD and PHA. Proportion of E-RFC was significantly lower in patients than in controls but was not found to correlate directly with the above functional criteria. Fifty-one percent of the patients with early, operable tumors were shown to be at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

1980
1980
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…6 From our study, it seems that if a lymph node has a hard consistency, then a negative Mantoux test and a positive abdominal ultrasound are more useful in predicting nodal malignancy. Negative Mantoux test has been shown to be associated with malignant conditions such as lymphomas, 7 cervical cancers with lymphadenopathy, 8 metastatic breast cancer 9 and colon and stomach cancer. 10 In causes of benign lymphadenopathy, like tuberculosis, studies have shown a very high positive rate of Mantoux in children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…6 From our study, it seems that if a lymph node has a hard consistency, then a negative Mantoux test and a positive abdominal ultrasound are more useful in predicting nodal malignancy. Negative Mantoux test has been shown to be associated with malignant conditions such as lymphomas, 7 cervical cancers with lymphadenopathy, 8 metastatic breast cancer 9 and colon and stomach cancer. 10 In causes of benign lymphadenopathy, like tuberculosis, studies have shown a very high positive rate of Mantoux in children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported similar findings. Adler et al (1980) found that small tumours with nodal involvement inhibited immune responsiveness more than those with no palpable homolateral axillary lymph nodes (NO).…”
Section: Discussionmentioning
confidence: 99%
“…Axillary nodes provide the first setting where antigen(s) released by the tumour stimulate the immunocompetent cells. Data from previous investigations suggest that locally-generated effector cells and their secretory products bring about a specific depression of the lymphocyte reactivity against non-tumour-related agents (recall antigens skin testing, PHA stimulation, mixed leukocyte reactions) (Whitthaker & Clark, 1971;Ellis et al, 1975;Whitehead et al, 1976;Nathanson, 1977;Adler et al, 1980;Cannon et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Während eine prognostische Relevanz der peritumorösen mononukleären Infiltrate sowie der reaktiven Veränderungen regionaler drainierender Lymphknoten als morphologische Zeichen einer immunologischen Auseinandersetzung zwischen Tumor und Tumorträger nahegelegt wird (4), sind die Ergebnisse zur prognostischen Bedeutung von Parametern der zellvermittelten Immunität sehr widersprüchlich. Während in einigen Arbeiten eine klinische Relevanz dieser Parameter nahegelegt wird (1,2,4,7,8,9,12,19,20,24,28), wird diese von anderen Autoren abgelehnt (9,14,26,27). Es wurde daher im Rahmen einer prospektiven Studie der Nachweis einer zellvermittelten Reaktion im LMI-Test mit der Ausbreitung des Tumors korreliert und durch engmaschige Nachsorgeuntersuchungen bezüglich seiner prognostischen Bedeutung analysiert.…”
Section: Introductionunclassified